One in four - Berry, Lucinda (Thomas & Mercer, 2025)
"Dr. Laurel Harlow can't believe she's agreed to do a reality TV show. But her years as a chemical dependency counselor and personal history with the show's director make her the obvious choice. Treating a mansion full of former child stars on the road to recovery is the tallest order of her career--especially when one of them turns up dead while the cameras are still rolling. In a house full of narcissists vying for the spotlight, everyone's hiding something...including Laurel. An investigation could expose a past she'd rather keep buried. But among the attention-starved patients, only one of them is a predator. And Laurel is skilled at spotting a predator when she sees one. As she hunts a killer in her present, the unsettling truths of Laurel's past are forced into the light. But this time, she'll face her demons head on. She'll stop at nothing to expose a murderer, even if it means risking everything she holds dear" --